Analisis Efektivitas Biaya Penggunaan Antibiotik Seftriakson dan Sefotaksim Pada Terapi Demam Tifoid di RSUD Dr.M.Ashari Pemalang - Dini Indriani; Musa Fitri Fatkhiya; Gita Ulistanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Typhoid fever is a disease caused by salmonella typhi bacteria whose main treatment is antibiotics. Antibiotic costs are more than 50% of the hospital pharmacy budged so that cost-effectiveness analysis is needed to improve efficiency or appropriate costs and effectiveness (treatment result). This study is an observation study on typhoid fever patients at Dr.M.Ashari Pemalang in January-Desember 2022. The sampling technique used purposive sampling and met the inclusion criteria of 20 samples. Data will be presented in tabular from on the data collection sheets and analyzed using the ACER formula and Microsoft excel. The result shower that ceftriaxone antibiotic therapy had a fever-free time o 3.30 days and a length of Hospitalization of 3.23 days while cefotaxime had a fever-free time o 3.71 days and a length o hospitalization 4.42 days. The ACER value obtained for ceftriaxone antibiotics is Rp 355,098.69 in length of hospitalization and Rp 347,566.30 in fever-free time while cefotaxime is Rp 393,348.92 in length of hospitalization and Rp 468,625.94 in fever-free time. From result it can be concluded that ceftriaxone antibiotics are more cost-effective than cefotaxime